Selectivity mechanism of GRK2/5 inhibition through in silico investigation. (December 2022) - Wu, Yiheng; Wang, Shizun; Wang, Hanxun; Hu, Baichun; Wang, Jian
Abstract: As two representative isoforms of G protein-coupled receptor kinases family, the largest known membrane receptor family, GRK2 and GRK5 are ubiquitously distributed in human heart, brain, lung, kidney, skeletal muscle and other tissues. GRK2 and GRK5 have common functions implicated in the regulation of heart failure, though GRK5 has also been involved in diseases like hypertension, cancer, diabetes and Alzheimer's disease. Therefore, to clarify the selectivity mechanism towards GRK2 and GRK5 will be of great significance for the discovery of effective and selective inhibitors. To this end, the structures and chemical properties of key residues were analyzed among GRK2 and GRK5 derived from their respective protein crystal structures. Furthermore, a combination of multiple computational strategies, including sequence superposition, receptor-ligand docking, molecular dynamics, MM-GBSA calculation, QM/MM approach and pharmacological modeling, were integrated to validated and elucidate their unique binding modes towards highly selective inhibitors. In addition, the specific amino acid distribution within the GRK2/5 target site is also analyzed in this paper, which can guide future research and development of selective inhibitors in a more targeted manner. Overall, our study comprehensively clarifies the selectivity mechanism of GRK2/5 inhibition, thereby providing guidance for further rational design of selective inhibitors targeting GRK2/5. Graphical Abstract: ga1 Highlights: The selectivity mechanism against GRK2/5 receptors is adequately investigated via in silico strategies. The binding modes of GRK2/5 receptors and their selective antagonists are fully explored using molecular docking and molecular dynamics simulations. The interactions formed by key residues and their stabilities are verified through molecular dynamics simulation. Various of analysis methods, such as MM-GBSA calculation, Hirshfled surface analysis, etc., confirm our conclusions, and the outcomes are as expected.